(untitled) (Revista Contexto & Saúde, 2023)
Objective: To identify the domains of essential health promotion competencies of the Competencies Health Promotion Project (CompHP) developed in the academic training of nursing in relation to LGBT health. Method: Descriptive and qualitative study, developed in three Higher Education Institutions in the interior of Ceará, Brazil, between July and December 2020, with 84 nursing students, through an online questionnaire. Data were organized using thematic content analysis and analyzed using the theoretical and methodological approach CompHP. Regarding ethical aspects, the study obtained a satisfactory opinion. Results: The age of the academics ranged from 21 to 47 years old, mostly female; cisgender women; heterosexuals; from private universities and enrolled in the ninth semester. Eight CompHP domains were identified: Possibility of Change; Health Advocacy; Partnership; Communication; Leadership; Diagnosis; Implementation and Evaluation and Research, the Planning domain being unidentified. The students are able to identify the health promotion demands of the LGBT public, however, even in the presence of the domains, they refer to the need for further discussion on the subject. Conclusion: The presence of eight of the nine domains of the CompHP was identified in the training of nursing students, which suggests that they can act as health promoting agents for the LGBT population.